Psychometric Evaluation of the Warwick-Edinburgh Mental Well-Being Scale on Indonesian Students - Ramadhana, Maulana Rezi (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Identification of mental health at the university is an important issue. This study aims to evaluate the psychometric performance of the Warwick-Edinburgh Mental Well-Being Scale (WEMWBS) as an instrument for assessing the mental health of students in Indonesia. The WEMWBS scale has validation in the UK, France, Norway, Spain, and China in various populations, and there needs to be clarity about the Indonesian version of the psychometric characteristics of WEMWBS in the student population. Four hundred twenty-three students from universities in Indonesia participated in this research. Internal consistency and scale factorial validity were examined after using the Indonesian version. All data analyses done by using SPSS version 23. The Indonesian version of WEMWBS showed high internal consistency (0.90). The results of the confirmatory analysis showed that only thirteen items could be grouped into one factor. between the Indonesian version of WEMWBS and the other scale. The findings of this study are essential for measuring students' mental health. These results can provide a reliable tool for evaluating mental health for students and have important implications for developing interventions in health promotion at the university.